2020
DOI: 10.1007/s11686-020-00258-3
|View full text |Cite
|
Sign up to set email alerts
|

First Detection and Molecular Identification of Entamoeba in Yaks from China

Abstract: Background Yak, a predominant livestock of plateau areas, is known as a host to many parasites. And the genus Entamoeba, the third-common cause of the mortality worldwide from parasitic diseases, was discovered in yaks once. Methods We investigated the distribution and species of Entamoeba spp. from yaks in Qinghai province, northwestern China, by collecting 1027 yak fecal samples. All samples were divided according to seven geographical sites, four seasons, and two age groups of yaks. After extracting DNA, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…In the current study, both microscopic and PCR analyses showed that 80% of the wild water buffaloes were infected with E. bovis . A study done in China showed that 100% of cattle and >90% of yak, goat and sheep were infected with E. bovis (Ren et al., 2021 ). E. bovis infection was detected in 80% of cattle and 60% of goats in a study conducted in Uganda (Nolan et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the current study, both microscopic and PCR analyses showed that 80% of the wild water buffaloes were infected with E. bovis . A study done in China showed that 100% of cattle and >90% of yak, goat and sheep were infected with E. bovis (Ren et al., 2021 ). E. bovis infection was detected in 80% of cattle and 60% of goats in a study conducted in Uganda (Nolan et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the intensification of GI symptoms by mixed parasite infection of ruminant Entamoeba spp. with other intestinal parasites (Matsubayashi et al., 2018 ; Ren et al., 2021 ). Therefore, further study is needed to determine the pathologic consequences of Entamoeba in mixed‐infection situations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations